Health financing and integration of urban and rural residents' basic medical insurance systems in China - Kun Zhu; Luying Zhang; Shasha Yuan; Xiaojuan Zhang; Zhiruo Zhang (BMC, 2017)
Abstract Background China is in the process of integrating the new cooperative medical scheme (NCMS) and the urban residents' basic medical insurance system (URBMI) into the urban and rural residents' basic medical insurance system (URRBMI). However, how to integrate the financing policies of NCMS and URBMI has not been described in detail. This paper attempts to illustrate the differences between the financing mechanisms of NCMS and URBMI, to analyze financing inequity between urban and rural residents and to identify financing mechanisms for integrating urban and rural residents' medical insurance systems. Methods Financing data for NCMS and URBMI (from 2008 to 2015) was collected from the China health statistics yearbook, the China health and family planning statistics yearbook, the National Handbook of NCMS Information, the China human resources and social security statistics yearbook, and the China social security yearbook. "Ability to pay" was introduced to measure inequity in health financing. Individual contributions to NCMS and URBMI as a function of per capita disposable income was used to analyze equity in health financing between rural and urban residents. Results URBMI had a financing mechanism that was similar to that used by NCMS in that public finance accounted for more than three quarters of the pooling funds. The scale of financing for NCMS was less than 5% of the per capita net income of rural residents and less than 2% of the per capita disposable income of urban residents for URBMI. Individual contributions to the NCMS and URBMI funds were less than 1% of their disposable and net incomes. Inequity in health financing between urban and rural residents in China was not improved as expected with the introduction of NCMS and URBMI. The role of the central government and local governments in financing NCMS and URBMI was oscillating in the past decade. Conclusions The scale of financing for URRBMI is insufficient for the increasing demands for medical services from the insured. The pooling fund should be increased so that it can better adjust to China's rapidly aging population and epidemiological transitions as well as protect the insured from poverty due to illness. Individual contributions to the URBMI and NCMS funds were small in terms of contributors' incomes. The role of the central government and local governments in financing URRBMI was not clearly identified. Individual contributions to the URRBMI fund should be increased to ensure the sustainable development of URRBMI. Compulsory enrollment should be required so that URRBMI improves the social medical insurance system in China.